Momordica Grosvenori Shell-Derived Porous Carbon Materials for High-Efficiency Symmetric Supercapacitors - Yunmeng You; Xianhao Hua; Yuanying Cui; Guiming Wu; Shujun Qiu; Yongpeng Xia; Yumei Luo; Fen Xu; Lixian Sun; Hailiang Chu (Nanomaterials, 2022)
Porous carbon materials derived from waste biomass have received broad interest in supercapacitor research due to their high specific surface area, good electrical conductivity, and excellent electrochemical performance. In this work, Momordica grosvenori shell-derived porous carbons (MGCs) were synthesized by high-temperature carbonization and subsequent activation by potassium hydroxide (KOH). As a supercapacitor electrode, the optimized MGCs-2 sample exhibits superior electrochemical performance. For example, a high specific capacitance of 367 F∙g−1 is achieved at 0.5 A∙g−1. Even at 20 A∙g−1, more than 260 F∙g−1 can be retained. Moreover, it also reveals favorable cycling stability (more than 96% of capacitance retention after 10,000 cycles at 5 A∙g−1). These results demonstrate that porous carbon materials derived from Momordica grosvenori shells are one of the most promising electrode candidate materials for practical use in the fields of electrochemical energy storage and conversion.